Wpływ technologii informacyjno-komunikacyjnych na strukturę organizacyjną przedsiębiorstw - Tabaszewska, Edyta (The influence of information and communication technologies on the organizational structure of enterprises, 2006)
The paper describes the main information tools and theirs influence on the organizational structure of enterprises. It also points to the role of organizational culture, management style and human resources in creating the enterprise which manages knowledge.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 86-97